NILAI KARATER FILM NUSSA DAN RARA DALAM PERSEPSI GURU SD NEGERI KECAMATAN BLADO KABUPATEN BATANG - Nur Koidah; Suyitno; Rofian (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The context of this research is to develop the basic potential to have a good heart, think well and behave well to build a multicultural nation. The process of instilling character education in students is not only through formal or non-formal schools, but the instilling of character education can be carried out using different educational media such as mass media, print and electronic media which includes audio, visual and audiovisual media. This research aims to determine the character values ​​in the animated film Nussa and Rara, and through this video it is hoped that it can educate students' characters so that they match the national character. The research was carried out in 28 elementary schools in Blado District, Batang Regency with 28 class III teachers. This research was conducted via WhatsApp chat by sending a video of the Nussa and Rara film episode "Good Is Easy" and a questionnaire to the class III teacher. From the research results obtained in the Nussa and Rara film episode "Good Is Easy" there were five values ​​of character education, namely religious, respect for achievement, curiosity, environmental care, social care. And 28 teachers from 28 Elementary Schools in Blado District, Batang Regency agreed regarding the value of character education contained in the Nussa and Rara films, because the film contains many character education values ​​that students can imitate and emulate.